KIBRA promoter methylation and association with clinical manifestation of renal cancer: A study in a tertiary institute in eastern India - Avisek Dutta; Biswabandhu Bankura; Madhusudan Das; Dilip Kumar Pal (Annals of Medical Science and Research)
Objective: This study aims at detecting KIBRA promoter methylation and association with clinic-pathological manifestations in renal cancer.